2015
DOI: 10.4238/2015.november.24.21
|View full text |Cite
|
Sign up to set email alerts
|

Keratins 17 and 19 expression as prognostic markers in oral squamous cell carcinoma

Abstract: ABSTRACT. Five-year survival rates for oral squamous cell carcinoma (OSCC) are 30% and the mortality rate is 50%. Immunohistochemistry panels are used to evaluate proliferation, vascularization, apoptosis, HPV infection, and keratin expression, which are important markers of malignant progression. Keratins are a family of intermediate filaments predominantly expressed in epithelial cells and have an essential role in mechanical support and cytoskeleton formation, which is essential for the structural integrity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 41 publications
2
16
0
Order By: Relevance
“…Further analysis by immunohistochemical technique revealed that CK17 was found in 100% of 39 OSCC tissue samples, whereas no staining was detected in normal oral mucosal tissue adjacent to cancerous tissue. Consistent with our study, several studies have demonstrated overexpression of CK17 both at gene and protein levels in OSCC compared with adjacent normal oral mucosa [ 3 , 6 10 ]. These results indicate that CK17 is an essential cytokeratin for OSCC and CK17 may be a good candidate to diagnose OSCC.…”
Section: Introductionsupporting
confidence: 93%
“…Further analysis by immunohistochemical technique revealed that CK17 was found in 100% of 39 OSCC tissue samples, whereas no staining was detected in normal oral mucosal tissue adjacent to cancerous tissue. Consistent with our study, several studies have demonstrated overexpression of CK17 both at gene and protein levels in OSCC compared with adjacent normal oral mucosa [ 3 , 6 10 ]. These results indicate that CK17 is an essential cytokeratin for OSCC and CK17 may be a good candidate to diagnose OSCC.…”
Section: Introductionsupporting
confidence: 93%
“…However, previous observations summarized by Presland and Dale support our findings and indicate that keratin 8 may be present in normal gingiva, especially in the junctional part of epithelium. Similarly, detection of keratins 17–19 can have some diagnostic relevance in study of oral epithelium dysplasia . However, it should be noted that basal expression of keratin 19 is also physiological in oral epithelium .…”
Section: Discussionmentioning
confidence: 99%
“…In neoplastic conditions, K17 is expressed in cervical carcinoma, breast carcinoma, gastric carcinoma, adenocarcinoma and squamous cell carcinomas (SCC) . In the cervix, K17 immunohistochemistry showed stronger expression in SCC and high‐grade squamous intraepithelial lesions than in normal squamous mucosa and low‐grade squamous intraepithelial lesions, suggesting K17 as a diagnostic marker to distinguish malignant cervical lesions from non‐malignant lesions or normal mucosa .…”
Section: K17 Dysregulation In Cancer Pathogenesismentioning
confidence: 99%